A Pipeline to Investigate Fungal–Fungal Interactions: Trichoderma Isolates against Plant-Associated Fungi - Marianna Dourou; Caterina Anna Maria La Porta (Journal of Fungi, 2023)
Soil fungi play essential roles in ecosystems, forming complex interaction networks with bacteria, yeasts, other fungi, or plants. In the framework of biocontrol strategies, Trichoderma-based fungicides are at the forefront of research as an alternative to synthetic ones. However, the impact of introducing new microbial strain(s) on the soil microbiome of a habitat is not well-explored. Aiming to identify a quantitative method to explore the complex fungal interactions, we isolated twelve fungi from three Italian vineyards and identified three strains of the Trichoderma genus in addition to nine more plant-associated fungi of different genera. Investigating in dual nucleation assay fungal–fungal interactions, we recognised two types of interaction: neutral or antagonistic. All three Trichoderma strains displayed a slight inhibitory behaviour against themselves. Trichoderma strains showed a mutually intermingling growth with Aspergillus aculeatus and Rhizopus arrhizus but antagonistic behaviour against the plant pathogens Alternaria sp., Fusarium ramigenum, and Botrytis caroliniana. Yet, in some cases, antagonistic behaviour by Trichoderma fungi was also observed against plant-promoting fungi (e.g., Aspergillus piperis and Penicillium oxalicum). Our study highlights the importance of studying the interactions between fungi, aiming to clarify better the impact of fungal-based biological fungicides in the soil communities, and offers a pipeline for further applications.